Analisis Pengajaran Dua Bahasa (Bilingual Education) terhadap Pemahaman Siswa pada Materi Ekosistem di SDK Gusung Karang Desa Koja Gete - Ahmad Alvian Sumarlin; Yulimira Syafriati Y.M Sani; Rofinus Galis (Universitas Palan, 2026)
Bilingual instruction is a learning strategy that can help students understand learning materials while bridging the gap between the language used at school and the language spoken in daily life. This study aims to analyze the effect of bilingual instruction on students' understanding of the Ecosystem topic at SDK Gusung Karang, Koja Gete Village. The study was motivated by the fact that students predominantly use the Sikka language in their daily communication, making it difficult for them to understand lessons delivered solely in Indonesian. This study employed a qualitative approach with a descriptive method. The research participants consisted of the fourth-grade homeroom teacher and fourth-grade students at SDK Gusung Karang. Data were collected through observations, interviews, and documentation and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that bilingual instruction has a positive impact on students' understanding of the Ecosystem topic. The use of the Sikka language helps students comprehend basic concepts, increases classroom participation, and enhances their confidence during the learning process. Meanwhile, Indonesian strengthens students' mastery of scientific terminology and academic language skills. Although students still experience difficulties in consistently using scientific terms in Indonesian, bilingual instruction improves their understanding and connects learning concepts with their real-life experiences. The effectiveness of this strategy depends on teachers' ability to manage language switching in a structured and consistent manner.